Winston-Salem debutants, 1957. - (:unkn) unknown (Forsyth County Public Library, 2009)
WSJ 12-28-57 p.5.
Winston-Salem debutants, 1957. The women are: Elizabeth Norman Whitaker and Elizabeth DeKalb Wylie.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth